2004
DOI: 10.1634/stemcells.22-5-741
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Telomerase Modulation in Human Hematopoietic Progenitor Cells

Abstract: Loss of telomeric repeats has been causally linked to replicative senescence and aging in human cells. In contrast to normal somatic cells, which are telomerase-negative, hematopoietic stem cells have low levels of telomerase, which can be transiently upregulated upon cytokine stimulation. To examine whether ectopic expression of telomerase can overcome telomere erosion in hematopoietic progenitor cells, we overexpressed telomerase in CD34 + and AC133 + cord blood (CB) cells using retroviral vectors containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 44 publications
(62 reference statements)
6
42
0
7
Order By: Relevance
“…1B). The stability of telomere length in hematopoietic cells during short-term culture has also been reported by others (31).…”
Section: Telomeres Of Normal Human Hematopoietic Cells Do Not Shortensupporting
confidence: 75%
“…1B). The stability of telomere length in hematopoietic cells during short-term culture has also been reported by others (31).…”
Section: Telomeres Of Normal Human Hematopoietic Cells Do Not Shortensupporting
confidence: 75%
“…The immortalization of WI38 by hTERT expression was documented in an earlier study (27); similarly, hTERT expression was found to be sufficient to immortalize HK1 cells (63). There is some conflict on the immortalization of IMR90 cells; however, under our laboratory conditions, we successfully established IMR90 cells in which the replicative senescence limit clearly was bypassed by hTERT overexpression (the cells were monitored until population doubling 115 [PD115]), in line with observations made by others (34; J. Shay, personal communication).…”
Section: Resultsmentioning
confidence: 57%
“…Retrovirus production and infection protocol Retroviral gene transfer of a DN mutant of hTERT was performed as recently described (Zimmermann et al, 2004;Pantic et al, 2005). HCT116 cells were infected with a DNhTERT-IRES-GFP and a pOS GFP control vector.…”
Section: Cell Linementioning
confidence: 99%